PERSUASIVE COMMUNICATION IN CULT-THEMED MOVIES: A SOCIO-PRAGMATIC STUDY - Bening Salsa Biela (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
The practice of cults has been proven to be dangerous to the mental health of the victims. This study analyzed and demonstrated some samples of persuasive communication techniques used by cults in recruiting and brainwashing their members in a cult-themed movie and a cult documentary, as well as their effects on the victims and how the victims respond to them. The study used a descriptive qualitative approach, and the data were taken from Midsommar and The Sacrament. The 70 data in words and non-verbal gestures were analyzed with a sociopragmatic approach, particularly Perloff's persuasive communication techniques, Miller's persuasive communication effects, and Cialdini's six basic human tendencies in responding to persuasive communication. This study found that 1) persuasive communication in Midsommar was dominated by using the interpersonal persuasion technique, whereas in The Sacrament was dominated by using the exact message, 2) the shaping effect dominated both movies and 3) the liking tendency dominated both. This study hopes to give an understanding among the readers and society about how persuasive the cults use communication to recruit and brainwash their targets so that they would not fall into the danger of cults in real life Keywords: brainwashing; cult; movie; persuasive communication; socio-pragmatics